Explaining general anesthesia: A two‐step hypothesis linking sleep circuits and the synaptic release machinery. (22nd January 2014) - van Swinderen, Bruno; Kottler, Benjamin
<x xml:space="preserve">Abstract</x> Several general anesthetics produce their sedative effect by activating endogenous sleep pathways. We propose that general anesthesia is a two‐step process targeting sleep circuits at low doses, and synaptic release mechanisms across the entire brain at the higher doses required for surgery. Our hypothesis synthesizes data from a variety of model systems, some which require sleep (e.g. rodents and adult flies) and others that probably do not sleep (e.g. adult nematodes and cultured cell lines). Non‐sleeping systems can be made insensitive (or hypersensitive) to some anesthetics by modifying a single pre‐synaptic protein, syntaxin1A. This suggests that the synaptic release machinery, centered on the highly conserved SNARE complex, is an important target of general anesthetics in all animals. A careful consideration of SNARE architecture uncovers a potential mechanism for general anesthesia, which may be the primary target in animals that do not sleep, but a secondary target in animals that sleep.